TATA KELOLA PERUSAHAAN PEMEGANG SAHAM TUNGGAL: KONSEP HUKUM DARI UNDANG-UNDANG CIPTA KERJA - Prasetyo, Abigail; Yanto, Oliviani; Ndruru, Dian (Universitas Kristen Satya Wacana, 2025)
This article will discuss the principles of good corporate governance and what good practices an individual company should adopt. An Individual Company is a legal entity that has only one shareholder in the company. The Job Creation Law legally recognizes this provision. In principle, the norm is incompatible with the concept of a limited liability company consisting of shares. Practically, the organs in an individual company will not be as ideal as the limited liability companies that have existed so far. On this basis, the issue to be discussed in this article is whether the management of an individual company in Indonesia is in accordance with the principles of good corporate governance. This article argues that an appropriate governance concept is needed so that individual companies can still run well based on good corporate governance principles.